The (Mis)Representation of Algerian Women in Proverbs - BEN HALIMA, El Alia (My University, 2019)
One of the most influential oral products in any society is the proverb. The latter has been the concern of sociolinguists for the fact that it has linguistic, social and cultural dimensions. The present dissertation sheds light on proverbs about women originated in the western towns of Algeria. It aims at revealing how the image of women is painted through investigating the perceptions and attitudes of West Algerians towards the negative and positive portrayals of women in the proverbs of their region. The researcher works on a corpus of twenty (20) proverbs about women. The collected proverbs are sociolinguistically analyzed. Moreover, a questionnaire is selected as a research instrument that investigates the attitudes of west Algerians towards proverbs that portray women. The informants are Algerian intellectuals of different ages and sexes. After the qualitative and descriptive analysis, the results have indicated that women are stereotypically portrayed more negatively, yet some social roles – like the mother- are respected in proverbs.
The Case of Proverbs in the Western Towns
Keywords: Proverbs; West Algeria; Portrayals; Attitudes; Mis/representation